Improved language performance in Alzheimer disease following brain stimulation. Issue 7 (23rd June 2010) - Cotelli, Maria; Calabria, Marco; Manenti, Rosa; Rosini, Sandra; Zanetti, Orazio; Cappa, Stefano F; Miniussi, Carlo
Abstract : Objectives: Repetitive transcranial magnetic stimulation (rTMS) has been proposed as a possible treatment for the cognitive deficits associated with Alzheimer disease (AD). The aim of this study was to assess the long-term effects, on cognitive performance, of rTMS applied to the left dorsolateral prefrontal cortex (DLPFC) in AD patients. Methods: Ten AD patients were randomly assigned to one of two study groups. Multiple-baseline design was used.The first group underwent a 4-week real rTMS stimulation protocol, while the second underwent a 2-week placebo treatment, followed by 2 weeks of real rTMS stimulation. Each session consisted of the application of rhythmic high-frequency rTMS over the DLPFC for 25 min. Sessions occurred once daily, 5 days/week. The main analysed outcome was the change in cognitive test performance at 2 and 4 weeks after rTMS treatment initiation, with a follow-up performed 8 weeks after the end of rTMS, in comparison with baseline performance. Results: A significant difference was found between groups over sessions in terms of the percentage of correct responses of auditory sentence comprehension. Only real treatment induced an improvement in performance with respect to baseline or placebo. Moreover, both groups showed a lasting effect on the improved performance 8 weeks after the end of treatment. Conclusion: The findings provide initial evidence for the persistent beneficial effects of rTMS on sentence comprehension in AD patients. Rhythmic rTMS, in conjunction with other therapeutic interventions, may represent a novel approach to the treatment of language dysfunction in AD patients.